Study of the efficiency of two strength program training in the Climbing's yield - G. Cuadrado; A.M. De Benito; G. Flor; J.M. Izquierdo; S. Sedano; J.C. Redondo (Asociación Española de Ciencias del Deporte, 2010)
The main aim of the current study was to determine the effectiveness of two strength training for climbing. 30 healthy men participated in the present study, and they were randomly divided into three groups: control group (GC) (n=10), maximal strength training group (GFM) and endurance-strength training group (GFR). The three groups trained three days per week, GC trained always in wall, but GFM and GFR changed one of them for a training session in the gym. The program lasted 10 weeks and we assesed different kinds of variables before and after the training: physical conditioning variables and hand-grip strength after climbing. We found significant differences in the three groups analysed. GFR obtained the best results according to climbing demands and GFM also obtained significant differences but not as specific as GFR. It could be said that endurance-strength training is the best for climbing. Key Words:Climbing, training, maximal strength, endurance-strength.